Septic arthritis of the temporomandibular joint after complication of facial cellulitis: case report - Sabelle, Nicole (2020)
Mandibular condyle infection, septic arthritis, is a disease characterized by pain, fever, edema, and functional decrease of the temporomandibular joint. It predominates in adult men and its etiology includes different factors: systemic diseases, autoimmune diseases, local trauma and spread of infections in the head and neck region. A clinical case of septic arthritis in the temporomandibular joint as a complication of infectious facial cellulitis is presented. Treatment consisted of antibiotic therapy and serial arthrocentesis with the aim of performing an intra-articular cleaning, accompanied by early mobilization of the joint, ideally with the support of a kinesiology team. In addition, long-term and periodic controls are very important in order to obtain a better clinical result in the patient, control in the long term, minimizing the risks of presenting a decrease in mandibular dynamics and / or ankylosis of the joint.